Train arrangement in scheduling for rail-rail transshipment yard - Grebennik, I.; Dupas, R.; Lytvynenko, O.; Urniaieva, I. (UNWE, 2017)
Article considers problem of scheduling freight trains in rail-rail transshipment yards. Besides scheduling the service slots of trains, article additionally solves the problem of train arrangement, i.e. assigning each train to a railway track. Mathematical model and solving method for described problem are given. The key feature of given mathematical model is that is uses combinatorial objects (tuples of permutations) instead of traditional Boolean variables. Solution method is based on generation of combinatorial sets as well, which is quite unusual approach comparing with existing solution methods for described problem.
Keywords: transshipment yard; freight transportation; train arrangement; combinatorial set; beam search; combinatorial generation